Weigth loss strategies - Magnus Benetti; Cristina Hauser; Fabiana Pereira V. Rebelo (Universidade Federal de Santa Catarina, 2004)
Although it does not represent a great isolated cause of death, obesity may be considered one of the greatest health problems nowadays because it is associated with several diseases. Inorder to avoid both increase and appearance of new cases of obesity, it is paramount that preventive measures should be taken. Prevention may be implemented through changes in lifestyle, such as eating habits re-education and the practice of physical exercises. The objective of this study was to review what type of physical exercise and also the strategies that may be adopted in exercise prescription of to optimize weight loss. It was observed that muscular resistance exercise combined with aerobic exercise seemed to produce the best results in weight loss programs because they help to increase resting metabolic rate, to keep and/or increase fat-free mass and optimize the rate of mobilization, and use of fat during weight loss. The weight loss goal seems to be successfully reached in programs that included resistance exercise, continuous and/or intermittent aerobic exercises which demand a high energy flow (70% VO2máx.). This process seemed to be more efficient because it afforded a greater total caloric expenditure; not only during exercise, but also because it triggered an increase in post-exercise oxygen consumption, thus causing fat to be used during this period. RESUMO A obesidade pode ser considerada um dos maiores problemas de saúde da atualidade por estar associada a inúmeras doenças, apesar de não representar uma grande causa isolada de morte. Para evitar tanto o crescimento como o surgimento de novos casos de obesidade, faz-se necessário que medidas de prevenção sejam tomadas. A prevenção é realizada através de mudanças no estilo de vida, como reeducação alimentar e inclusão da prática de exercícios físicos. O objetivo desta revisão foi abordar qual o tipo de exercício físico e também as estratégias que podem ser adotadas na prescrição do exercício para otimizar o processo de perda de peso. Observou-se que os exercícios de resistência muscular combinados com o exercício aeróbio, pareceram alcançar os maiores resultados nos programas de perda de peso, por auxiliar no aumento da taxa metabólica de repouso, manter e/ou aumentar a massa muscular e otimizar os índices de mobilização e utilização de gordura durante o emagrecimento. O objetivo de emagrecimento parece ser alcançado com êxito em programas que incluem exercícios de resistência, exercícios aeróbios intermitentes e/ou contínuos que utilizem um alto fluxo de energia (70% do VO2 máx.). Este processo pareceu ser mais eficiente por proporcionar um maior gasto calórico total; não somente durante a realização do exercício, mas também por provocar um aumento no consumo de oxigênio pós-exercício, fazendo com que a gordura seja utilizada neste período.